(untitled) (Journal on Geoinformatics, Nepal, 2024)
Flood disasters annually devastate livelihoods, particularly during the monsoon season, with no apparent reduction in impacts in low-lying regions of developing countries like Nepal. Given the increasing effects of climate change globally, this study aims to assess climate change effects and biophysical vulnerability of riverine communities to floods in the Narayani River of Nepal, elucidating the interrelationship between these phenomena. This paper presents an analysis of trends and extreme events of climatological variables, such as temperature, precipitation, and daily river discharge and hazard mapping and risk assessments in the river stretch of two Village Development Committees (VDCs) in the country’s inner Terai region of Nawalparasi district for different return-period floods, with the aid of the HEC-RAS (Hydrologic Engineering Centre’s River Analysis System) and HEC-GeoRAS. A long-term climatological data was collected from the Department of Hydrology and Meteorology, Kathmandu, and the analysis was performed using statistical softwares, SigmaStat, and SigmaPlot. In addition, flood conditions representing 2, and 100-year periods were determined using Gumbel’s distribution. The study revealed a narrowing temperature range, with increasing minimum temperatures and decreasing maximum temperatures, precipitation, and river discharge. However, there was a notable increase in extreme events. The hazard mapping indicated the people’s vulnerability to inundation and soil erosion along the low-lying riverbanks. The findings underscore the necessity for reliable technological and socio-economic vulnerability mapping to provide early warnings to at-risk populations. This paper argues that unplanned and mismanaged settlements in riverine areas may lead to population displacements, creating environmental refugees.